Pregnancy imparts distinct systemic adaptive immune function. (6th September 2022) - Demery‐Poulos, Catherine; Romero, Roberto; Xu, Yi; Arenas‐Hernandez, Marcia; Miller, Derek; Tao, Li; Galaz, Jose; Farias‐Jofre, Marcelo; Bhatti, Gaurav; Garcia‐Flores, Valeria; Seyerle, Megan; Tarca, Adi L.; et al.
Abstract: Problem: Pregnancy represents a state of systemic immune activation that is primarily driven by alterations in circulating innate immune cells. Recent studies have suggested that cellular adaptive immune components, T cells and B cells, also undergo changes throughout gestation. However, the phenotypes and functions of such adaptive immune cells are poorly understood. Herein, we utilized high‐dimensional flow cytometry and functional assays to characterize T‐cell and B‐cell responses in pregnant and non‐pregnant women. Methods: Peripheral blood mononuclear cells from pregnant (n = 20) and non‐pregnant (n = 25) women were used for phenotyping of T‐cell and B‐cell subsets. T‐cell proliferation and B‐cell activation were assessed by flow cytometry after in vitro stimulation, and lymphocyte cytotoxicity was evaluated by using a cell‐based assay. Statistical comparisons were performed with linear mixed‐effects models. Results: Pregnancy was associated with modestly enhanced basal activation of peripheral CD4 + T cells. Both CD4 + and CD8 + T cells from pregnant women showed increased activation‐induced proliferation; yet, a reduced proportion of these cells expressed activation markers compared to non‐pregnant women. There were no differences in peripheral lymphocyte cytotoxicity between study groups. A greater proportion of B cells from pregnant women displayed memory‐like and activated phenotypes, and such cells exhibited higher activation following stimulation. Conclusion: Maternal circulating T cells and B cells display distinct responses during pregnancy. The former may reflect the unique capacity of T cells to respond to potential threats without undergoing aberrant activation, thereby preventing systemic inflammatory responses that can lead to adverse perinatal consequences.